Det Regionale I Det Internasjonale 2018
DOI: 10.18261/9788215031224-2018-17
|View full text |Cite
|
Sign up to set email alerts
|

Kapittel 17: Does country-of-origin image and ethnocentrism positively influencethe home market brand equity for the brand Dybvik?

Abstract: SAMMENDRAG Studien analysere effekter av konsumenters oppfatninger av image til opprinnelsesland (COOI) og etnosentrisme på oppfattet verdi til klippfiskmerket Dybvik. En markedsundersøkelse med 333 respondenter er analysert v.h.a. PLS-SEM for å svare på følgende problemstilling: Påvirker oppfattet COOI og etnosentrisme klippfiskmerket Dybvik positivt på hjemmemarkedet? Begge variabler har positiv effekt på oppfattet merkeverdi, men i ulik grad i forhold til merkeverdiens underliggende dimensjoner.ABSTRACT The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It is reflected in the percentage of variance for the brand image, which only reaches 6.8%. The future research may also refer to research by Nervik et al, (2018), who found that in addition to consumer ethnocentrism, the brand image is also influenced by country-of-origin image and recent consumer experience.…”
Section: Limitationsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is reflected in the percentage of variance for the brand image, which only reaches 6.8%. The future research may also refer to research by Nervik et al, (2018), who found that in addition to consumer ethnocentrism, the brand image is also influenced by country-of-origin image and recent consumer experience.…”
Section: Limitationsmentioning
confidence: 97%
“…This study integrates all factors that can affect consumer ethnocentrism, animosity, religiosity, and allocentrism (Tabassi et al, 2012;Selli & Kurniawan, 2014;Nervik et al, 2018) to predict the purchase intention of Indonesian customer, mediated by the brand image. The new research framework provides a comprehensive view of how consumer ethnocentrism influences the behaviour of the customer.…”
Section: Purchase Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethnocentrism can be defined as the phenomenon where consumers prefer to purchase domestic products, or avoid purchasing imported products (Sharma et al, 1995). Ethnocentrism makes consumers reluctant to purchase imports, since they perceive that doing so may negatively affect their country's economy (Dursun et al, 2019;Nervik et al, 2018). Since consumer ethnocentrism influences consumers' decision-making processes, importers and exporters have to consider the level of ethnocentrism in their target consumer market when making international marketing decisions.…”
Section: ⅰ Introductionmentioning
confidence: 99%